Public Financial Management System in Meulaboh City - West Aceh (Relevance of the Review of Abu Yusuf & Abu Ubaid's Thought) - Susi Herawati; Azhari Akmal Tarigan; Muhammad Ridwan (Brilliant International Journal Of Management And Tourism, 2025)
In this study the results of the study showed that the Islamic economic system in the classical era, namely the thought of Abu Yusuf and Abu Ubaid was still relevant in the management of public finances in contemporary times. The thoughts of Abu Yusuf and Abu Ubaid about the management of public finances can be a philosophical and theoretical foundation for financial management in the city of West Meulaboh-Aceh. The principles of justice, efficiency, transparency, and people's welfare that they convey can be applied in managing the budget and public financial policy in the city of West Meulaboh-Aceh, to achieve sustainable development goals. The method in this study uses historical qualitative and literature study analysis. This approach shows that classical thoughts are still relevant to date, so that it can be a foundation as a system in managing public financial in government.